CBAM, Hydrogen Partnerships and Egypt's Industry: Potential for Synergies - Alexandra Gritz; Guntram B. Wolff (Intereconomics, 2024)
This article examines the hydrogen partnerships between Germany, the EU and Egypt in the context of the EU's Carbon Border Adjustment Mechanism (CBAM). Germany, the largest future hydrogen importer in the EU, and Egypt, a country with an ambitious hydrogen strategy, are developing a partnership to boost renewable hydrogen production in Egypt. However, high funding costs are a barrier to capital-intensive investments in hydrogen projects, in particular in emerging economies. CBAM provides an incentive to decarbonise but faces resistance in emerging economies as it may undermine the competitiveness of emission-intensive local production. Combining industrial development with hydrogen production could be a more promising partnership strategy than a narrow one focused only on producing hydrogen for export to the EU. By aligning hydrogen partnerships with local development goals, CBAM acceptance can be improved, as industrial development could be climate-friendly, making exports into the EU easier while creating new value chains to the benefit of EU producers.
Keywords: Q48; F18; O14; 330; Hydrogen; Hydrogen economy; Egypt; Germany; EU member states; Wasserstoff; Wasserstoffwirtschaft; Ägypten; Deutschland; EU-Staaten